Leadership skills and its relation on employees' job performance: Findings from the study at Ministry of Women, Family and Community Development at Putrajaya / Wan Nor Azleen Wan A. Rahman and Marni Ghazali - Wan A. Rahman, Wan Nor Azleen; Ghazali, Marni (2021)
Leadership is one of the leaders' processes as a social influence (Nanjundeswaraswamy & Swamy, 2014). Meanwhile, leadership is one of the imperative competencies required for an individual who wants to be a leader in the future and make the individual an effective leader towards their organizations (Overbay, 2017). Prior studies also highlighted that leaders need leadership skills which a leader must be capable to be function at all levels since the skill which were possessed by the leader can be developed either formal or informal through experience, readings, courses, and continuous learning that should be learned by the leaders (Mohamad & Silong, 2008). Meanwhile, poor leadership could be one of the major reasons for the organization's failure in achieving its goals (Mundhe, 2018). In South-East Asia countries, leadership has become one of the most critical talent issues which are about 97% of the Deloitte Global Human Capital Trends 2016 mentioned that the business leaders have considered that they need to develop their leaders in their organization fast and deeply (The Malaysian Reserve, 2017).